ALI SHARI’ATI ON DIVINE HUMANISM: INTEGRATION OF DIVINE VALUES IN THE FORMATION OF HUMAN IDENTITY - Hotmatua Paralihan (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2024)
Divine Humanism, initiated by Ali Shari’ati, offers an integrative view of forming human identity based on divine values. In this view, humans are understood not only as material entities but also as spiritual beings with moral responsibilities towards themselves, society, and God. Shari’ati emphasizes that the unity between humans, nature, and God is the foundation for building a complete human identity. This study aims to explore and understand the concept of divine Humanism in Ali Shari’ati’s thought, focusing on key works such as Man and Islam, Religion vs. Religion, and Marxism and Other Western Fallacies. The study explores the core ideas, principles, and implications of divine Humanism and how divine values contribute to forming human identity. It found that humans are considered material and spiritual beings with moral responsibilities towards God, self, and society. The concept of tawhid, which emphasizes the unity of God, man, and nature, is the basis of a complete human identity. Shari’ati's divine humanism criticizes secularism and secular humanism, which ignore spirituality, fuel moral crises, ethical relativism, and alienation. As an alternative, he places divine values such as justice, compassion, and social responsibility at the core of human identity and the driver of social transformation. This study makes an important contribution to global social issues by offering Ali Shari‘ati’s divine humanism approach as a framework for understanding and overcoming the challenges of modernity, such as dehumanization, moral crisis, and ethical relativism.